What underwear do I like?’ Taste and (embodied) cultural capital in the consumption of women’s underwear - Tsaousi, Christiana (My University, 2016)
This paper argues that women’s underwear functions as a source for (re)constructing female identity, and that women’s consumption of underwear is an embodied experience through which they ‘learn’ to choose the ‘right’ underwear for the right occasion. This experience is understood here through the use of Pierre Bourdieu’s notions of habitus, taste and (embodied) cultural capital, thus expanding the limited literature on underwear and its significance in terms of identity and consumption. Through a series of focus groups and interviews, I argue that women express their taste in underwear depending on their habitus-influenced assumptions about its role and function, and that underwear works as their embodied cultural capital to support elements of female identity. The themes of my analysis include the degree to which my participants exhibit their sense of taste about the underwear they buy, and how they distinguish between the underwear that they need to wear in particular fields; the transmission of their mothers’ cultural capital and taste when it comes to their choices in underwear; and the relationship between underwear and outerwear, and how they use the former to support their dress within specific fields or contexts they move in and out of in their daily lives.
Keywords: Bourdieu; Embodied cultural capital; Habitus; Identity construction; Taste; Underwear